1990
DOI: 10.1083/jcb.110.6.1885
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BiP/GRP78 function blocks translocation of secretory proteins in yeast.

Abstract: Abstract. BiP/GRP78 is an essential member of the HSP70 family that resides in the lumen of the endoplasmic reticulum. In yeast, BiP/GRP78 is encoded by the KAR2 gene. A temperature sensitive mutation was isolated in KAR2 and found to cause a rapid block in protein secretion. Secretory precursors of a number of proteins (invertase, carboxypeptidase Y, a-factor, and BiP) accumulated that were characteristic of a block in translocation into the lumen of the ER. Protease protection experiments confirmed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
304
1
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 428 publications
(311 citation statements)
references
References 48 publications
5
304
1
1
Order By: Relevance
“…We also observed accumulation of an unglycosylated form of CPY only in the type A mutant cells (unpublished data). These findings are consistent with previous reports (Vogel et al, 1990;Sanders et al, 1992) and suggest that type A and type S mutants correspond to the class I and class II kar2 mutants, respectively, defined by Brodsky and Rose (1997), based on their phenotypes. These observations strongly suggest that protein translocation into the ER is blocked only in the type A mutant strains.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…We also observed accumulation of an unglycosylated form of CPY only in the type A mutant cells (unpublished data). These findings are consistent with previous reports (Vogel et al, 1990;Sanders et al, 1992) and suggest that type A and type S mutants correspond to the class I and class II kar2 mutants, respectively, defined by Brodsky and Rose (1997), based on their phenotypes. These observations strongly suggest that protein translocation into the ER is blocked only in the type A mutant strains.…”
Section: Discussionsupporting
confidence: 82%
“…Anti-HA Western blot analysis of the cell lysates indicated that Ire1-HA was expressed at similar levels in all of the kar2 mutant and control wild-type strains (Figure 3, uppermost panel). The precursor form of Kar2 (pre-Kar2) was detected in lysates from the type A mutant cells by anti-Kar2 Western blotting (Figure 3, second panel, lanes 4 -9), suggesting that protein translocation is impaired in these cells (Vogel et al, 1990).…”
Section: Impaired Association and Dissociation Of Kar2 And Ire1 In Kamentioning
confidence: 99%
See 2 more Smart Citations
“…Genes encoding homologues of mammalian SRP or SRP receptor components have been identified (Felici et al, 1989;Hann et al, 1989Hann et al, , 1992Amaya et al, 1990;Ogg et al, 1992;Stirling and Hewitt, 1992), and depletion of these homologs causes a translocation defect in vivo (Amaya and Nakano, 1991;Hann and Walter, 1991;Ogg et al, 1992;Stirling and Hewitt, 1992). Mutations in four essential genes (SEC61, SEC62, SEC63, and KAR2) are associated with translocation defects Schekman, 1987, 1989;Toyn et al, 1988;Sadler et al, 1989;Vogel et al, 1990;, and genetic and biochemical evidence indicates physical interactions between their protein products Deshaies et al, 1991;Scidmore, Okamura, and Rose, unpublished data). Sec6lp, Sec62p, and Kar2p can be cross-linked to translocating polypeptide chains in yeast ER membranes (Musch et al, 1992;Sanders et al, 1992), suggesting that they comprise components of a common translocation apparatus.…”
Section: Introductionmentioning
confidence: 99%